Grain yield stability of some exotic rice genotypes grown in the White Nile State, Sudan - A. Mohamed, Khalid; S. Ibrahim, Abu Elhassan; M. Mustafa, Ahmed (Gezira Journal of Agricultural Science, 2022)
Sixteen exotic genotypes of rice ( Oryza sativa L.) were evaluated across two locations ( Ed-duim and Kosti) for two years (2008 and 2009), for their grain yield and stability performance to identify high yielding and stable genotypes . A randomized complete block design with three replicates was used in each location. Significant differences were observed for genotypes (G), locations (E) and G x E interaction. All the genotypes gave high grain yield which ranged from 2.17 to 4.03 t ha -1 under irrigated conditions. Two genotypes ( i.e., NERICA 14 and YUNLU 33) were classified as high yielding and stable genotypes across environments (locations and years) because of their high grain yield, with a regression coefficient close to unity, relatively low mean square deviation from regression, low ecovalence value and top average ranking.    اختبرت 16 سلالة أرز مستوردة في موقعين (الدويم وكوستى) خلال عامي (2008 و 2009) لتحديد أكثر هذه السلالات إنتاجية وثباتاً في الإنتاجية. استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات في كل موقع. أظهرت نتائج تحليل التباين المشترك فروقات معنوية في السلالات و الموقع والتفاعل بين السلالات والموقع. كل السلالات أعطت إنتاجية عالية حيث تراوحت بين 2.17-4.03 طن/هكتار تحت ظروف الري. صنفت السلالتان NERICA 14, YUNLU 33) ) كأعلى الأصناف إنتاجية وثباتاً في الإنتاجية خلال البيئات (المواقع والسنين) لأنها أعطت أعلى إنتاجية، معامل انحدار اقرب للواحد الصحيح،  أقل متوسط مربع انحراف عن الانحدار واقل قيم ل Wi ) ) واعلى ترتيب للمتوسطات.